Is aquaculture pro-poor? Empirical evidence of impacts on fish consumption in Bangladesh - Toufique, K.A.; Belton, Ben (Elsevier, 2014)
Aquaculture is widely held to contribute to poverty reduction and food security in the Global South, but robust evidence is limited. Using nationally representative data from Bangladesh, this study analyses changes in fish consumption from 2000 to 2010. Rapid expansion of commercial aquaculture pegged down fish prices, resulting in increased fish consumption by extreme poor and moderate poor consumers and those in rural areas. These outcomes are closely linked to the pro-poor nature of national economic growth during this period. These findings contribute to a broadening of the debate on whether the growth of aquaculture in Bangladesh has been pro-poor.